Hydrophobic Fluorescent Probes Introduce Artifacts into Single Molecule Tracking Experiments Due to Non-Specific Binding - Zanetti-Domingues, Laura C.; Tynan, Christopher J.; Rolfe, Daniel J.; Clarke, David T.; Martin-Fernandez, Marisa (PLOS ONE, 2013)
Single-molecule techniques are powerful tools to investigate the structure and dynamics of macromolecular complexes; however, data quality can suffer because of weak specific signal, background noise and dye bleaching and blinking. It is less well-known, but equally important, that non-specific binding of probe to substrates results in a large number of immobile fluorescent molecules, introducing significant artifacts in live cell experiments. Following from our previous work in which we investigated glass coating substrates and demonstrated that the main contribution to this non-specific probe adhesion comes from the dye, we carried out a systematic investigation of how different dye chemistries influence the behaviour of spectrally similar fluorescent probes. Single-molecule brightness, bleaching and probe mobility on the surface of live breast cancer cells cultured on a non-adhesive substrate were assessed for anti-EGFR affibody conjugates with 14 different dyes from 5 different manufacturers, belonging to 3 spectrally homogeneous bands (491 nm, 561 nm and 638 nm laser lines excitation). Our results indicate that, as well as influencing their photophysical properties, dye chemistry has a strong influence on the propensity of dye-protein conjugates to adhere non-specifically to the substrate. In particular, hydrophobicity has a strong influence on interactions with the substrate, with hydrophobic dyes showing much greater levels of binding. Crucially, high levels of non-specific substrate binding result in calculated diffusion coefficients significantly lower than the true values. We conclude that the physic-chemical properties of the dyes should be considered carefully when planning single-molecule experiments. Favourable dye characteristics such as photostability and brightness can be offset by the propensity of a conjugate for non-specific adhesion.